Selenium and Natural Zeolite Clinoptilolite Supplementation Increases Antioxidative Status and Immune Response in Growing Pigs - Šperanda, Tomislav; Pavić, Valentina; Lončarić, Zdenko; Šperanda, Marcela; Popović, Maja; Gantner, Vesna; Ðidara, Mislav (Frontiers in Veterinary Science, 2021)
1 Introduction Selenium (Se), an essential trace element for human and animal health, is covalently incorporated into amino acids, acts as a cofactor for antioxidant enzymes, and is involved in the maintenance of the immune system. The main goal of this investigation was to show the effect of Se supplementation, at levels slightly higher than the recommended values, combined with natural zeolite clinoptilolite on Se deposition in tissues (muscle and liver) and on the immune and antioxidative status of supplemented growing pigs. The experiment was carried out during a 98 d period in 80 pigs (crossbred WJxSLxP) with equal sex distribution and body weight in the range of 28 kg to 98 kg. Pigs were fed a standard feed mixture based on corn and soybean and were divided into four groups, according to the level of dietary selenium supplementation as follows: C-0.3 mg/kg organic Se, E1-0.5 mg/kg sodium selenite, E2- 0.5 mg/kg organic selenium; E3-0.5 mg/kg organic Se+0.2% zeolite. Significantly higher (P<0.05) selenium concentrations were determined in the muscle and liver in the E2 and E3 groups compared with the E1 group, and in the E3 group compared with the C group. Significantly (P˂0.05) higher proportion of CD45+ pigs was observed in the E2 and E3 groups compared with the C and E1 groups. A higher (P<0.05) proportion of CD21+ lymphocytes was measured in the E2 and E3 groups compared with the other groups. It seems that natural zeolite clinoptilolite supported the influence of Se on the total ratio of CD45+, CD4+, and consequently CD21+ lymphocytes. The highest (P˂0.01) activity of glutathione peroxidase in pig erythrocytes was observed in the E3 group.